2015
DOI: 10.1183/09031936.00226614
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-hydroxyvitamin D level, smoking and lung function in adults: the HUNT Study

Abstract: The association between serum 25-hydroxyvitamin D (25(OH)D) level and lung function changes in the general population remains unclear.We conducted cross-sectional (n=1220) and follow-up (n=869) studies to investigate the interrelationship of serum 25(OH)D, smoking and lung function changes in a random sample of adults from the Nord-Trøndelag Health (HUNT) Study, Norway.Lung function was measured using spirometry and included forced expiratory volume in 1 s (FEV1) % predicted, forced vital capacity (FVC) % pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…Firstly, among Korean subjects a positive correlation between 25(OH)D and lung function was found [12] which was confirmed in the present study as well as in the Framingham Heart Study [10]. However, among a large Danish population of 3471 subjects no relation between 25(OH)D levels and lung function was detected [9] and Larose et al [8], comparing non-smokers with smokers, also did not observed an association between serum 25(OH)D levels and lung function or changes in lung function among non-smokers, while significant associations became apparent among smokers. Moreover, in a longitudinal analysis of the Framingham Heart Study no relation between 25(OH)D levels and FEV 1 was observed.…”
Section: Vitamin D and Lung Functionsupporting
confidence: 89%
“…Firstly, among Korean subjects a positive correlation between 25(OH)D and lung function was found [12] which was confirmed in the present study as well as in the Framingham Heart Study [10]. However, among a large Danish population of 3471 subjects no relation between 25(OH)D levels and lung function was detected [9] and Larose et al [8], comparing non-smokers with smokers, also did not observed an association between serum 25(OH)D levels and lung function or changes in lung function among non-smokers, while significant associations became apparent among smokers. Moreover, in a longitudinal analysis of the Framingham Heart Study no relation between 25(OH)D levels and FEV 1 was observed.…”
Section: Vitamin D and Lung Functionsupporting
confidence: 89%
“…No correlation was found of ventilatory parameters with 25(OH)D concentration in the study and control groups. Some researchers have reported statistically significant correlation in various subgroups of both controls and COPD patients [16][17][18]. The publications have lacked critical cause-and-effect analysis: decreased spirometric parameters have meant decreased physical fitness, less exposure to UV-B, and thus lower 25(OH)D concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for not finding a correlation of ventilatory parameters with 25(OH)D concentration may be a relatively small number of participants in the study group in comparison to the quoted articles (NHANES: more than 10,000 participants). An alternative reason for lack of correlation between activity parameters and 25(OH)D concentrations might be accurate characteristics, homogenousness and narrowing of the study group (patients with very severe COPD in the stage of respiratory failure), while in other studies [16][17][18], the population was not limited to COPD and patients were in various stages of disease, which might have facilitated the observation of a connection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intra-assay coefficient of variation and the inter-assay coefficient of variation of our samples were low, 4% and 8%, respectively. We categorized serum 25(OH)D as < 50, 50-74.9 and ≥ 75 nmol/L, and as per 25 nmol/L decrease based on previous literature [20][21][22][23].…”
Section: Serum 25(oh)dmentioning
confidence: 99%